Neuromechanical control of locomotion in larval Manduca sexta - Vaughan, Samuel Cordes (Tufts Archival Research Center, 2005)
Larval Manduca sexta, the tobacco hornworm, are remarkable climbers and crawlers. They have evolved to navigate up, down, and across branched and highly variable terrain: tobacco plants. In order to maintain motion, they must have one or more motor strategies, but the must be able to move in virtually limitless orientations. They are also interesting because Manduca sexta are completely soft and lack any rigid support structure. This research explored how larval Manduca sexta move in vertical and horizontal orientations. A finding of this research was that the proleg gripping system is used to provide a passive resistance to pitch back. Kinematic study of the proleg withdrawal mechanism was then used to determine how robust release is accomplished. This study found that they animals are able to move the gripping hooks on their feet inward, presumably to release tension on the hooks before withdrawal.